COVID-19 IN INVESTMENT ARBITRATION. A LEGAL ANSWER - Krzizok, Bianca Maria (Prudentia Iuris, 2021)
During today’s situation of COVID-19, States take emergency measures which will be subject to investment arbitration claims sooner or later. The aim of this paper is to provide a possible solution to such cases where the State’s and the investor’s interests compete with each other. By analysing cases from the 21th century and applying my findings to hypothetical COVID-19 cases, a general answer on how to solve COVID-19 related investment disputes shall be given.